Performance-Based Specifications for Sustainable Pavements: A Lean Engineering Analysis. (August 2015) - Hamdar, Yara; Kassem, Hussein; Srour, Issam; Chehab, Ghassan
Abstract: Lean concepts, though born in the manufacturing industry, have since made their way to the construction industry. In a broad sense, lean concepts aim at minimizing waste and maximizing value which can be related to cost, quality, and time. These aims are in-line with sustainable construction processes which target reducing the waste (e.g. resource consumption and emissions) in construction activities. As such, lean should not be viewed as a set of tools and techniques, but rather an approach and conceptual framework that can be catered to suit the needs of the process under study. Implementing lean concepts in the building construction sector has been proven challenging due to the uniqueness of each project. In infrastructure projects, such as pavements and bridges, the application of lean concepts is at its infancy stages and thus is still not well assessed and researched. The focus of this study is to investigate the implementation of lean concepts in pavement construction, specifically in the quality assurance/quality control (QA/QC) process. The ultimate objective is to come up with conclusions on how to maximize the value of pavements as dictated by their performance, while minimizing wastes due to inefficient QA/QC.